Government and Pesantren: The Dilemma of Formalization and Informalization in Islamic Education in Indonesia - Novita, Yanti; Kustati, Martin; Sepriyanti, Nana (Sekolah Tinggi Ilmu Tarbiyah (STIT) Ahlussunnah Bukittinggi, 2025)
This study analyzes the conceptual and practical tensions between government formal policies and the informal character of pesantren in the transformation of Islamic education in Indonesia. Although Law No. 18 of 2019 provides formal legitimacy for pesantren, the relationship between the government and pesantren does not operate linearly. Formalization through standardized curricula, accreditation, competency certification, and administrative obligations has created new dynamics within pesantren, which were previously based on non-bureaucratic traditions such as sorogan, bandongan, and halaqah. Many pesantren respond to these policies through adaptive strategies: accepting certain aspects of formalization to gain legitimacy and funding, while maintaining informal structures as the core of their identity. This research employs a qualitative approach, including document analysis, in-depth interviews, and participatory observation in both salafiyah and khalafiyah pesantren. The findings indicate that the formalization-informalization dilemma is a dialectical process involving adaptation, resistance, and compromise. The study underscores that the sustainability of pesantren depends on their ability to develop a hybrid education model that accommodates the demands of modernity without compromising foundational traditions.